1978
DOI: 10.1051/rnd:19780336
|View full text |Cite
|
Sign up to set email alerts
|

The movement of fluid in the seminiferous tubules and rete testis

Abstract: Summary. The composition of fluid from the seminiferous tubules and rete testis of the rat has been studied. Differences in ionic, steroid and protein concentrations in the two fluids suggest that two different fluids are secreted, but from the numbers of sperm and the concentrations of inositol, it now seems more likely that all the fluid is secreted in the seminiferous tubules but that its composition is modified as it passes through the tubuli recti or when it reaches the rete testis. The permeability of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 23 publications
(15 reference statements)
4
16
0
Order By: Relevance
“…A similar change takes place in the seminiferous ductules in vivo (Setchell, Davies, Gladwell, Hinton, Main, Pilsworth & Waites, 1978). Thus this might be a general property of the proximal male excurrent duct and it also suggests that our findings in vitro may have a counterpart in vivo.…”
Section: Discussionmentioning
confidence: 52%
“…A similar change takes place in the seminiferous ductules in vivo (Setchell, Davies, Gladwell, Hinton, Main, Pilsworth & Waites, 1978). Thus this might be a general property of the proximal male excurrent duct and it also suggests that our findings in vitro may have a counterpart in vivo.…”
Section: Discussionmentioning
confidence: 52%
“…However, when differences in the concentration of Na and K were compared in STF (free-flow micropuncture samples) and in RTF (collected by cannulation), it was estimated that only 20%-30% of the latter would originate from the seminiferous tubules [5,7]. Also, Setchell et al [14] showed that direct counts of sperm concentrations (as opposed to spermatocrit determinations) and inositol concentrations were similar in rat STF and RTF. Consequently, the two-fluid theory was rejected, and it was interpreted that testicular fluid is derived from secretions of the seminiferous tubules but that the fluid must be modified substantially by considerable solute secretion and reabsorption in the rete testis [3,5].…”
Section: Introductionmentioning
confidence: 98%
“…The former possibility is unlikely because micropuncture studies revealed similar concentrations of sperm and inosi tol in both fluids [Hinton et al. 1977: Setchell et al. 1978.…”
Section: Structural and Functional Relationships Of Epithelial Cellsmentioning
confidence: 99%